The Validation of a New Visual Anaemia Evaluation Tool HemoHue HH1 in Patients with End-Stage Renal Disease - Robert M. Kalicki; Stefan Farese; Dominik E. Uehlinger (Anemia)
In chronic haemodialysis patients, anaemia is a frequent finding associated with high therapeutic costs and further expenses resulting from serial laboratory measurements. HemoHue HH1, HemoHue Ltd, is a novel tool consisting of a visual scale for the noninvasive assessment of anaemia by matching the coloration of the conjunctiva with a calibrated hue scale. The aim of the study was to investigate the usefulness of HemoHue in estimating individual haemoglobin concentrations and binary treatment outcomes in haemodialysis patients. A prospective blinded study with 80 hemodialysis patients comparing the visual haemoglobin assessment with the standard laboratory measurement was performed. Each patient’s haemoglobin concentration was estimated by seven different medical and nonmedical observers with variable degrees of clinical experience on two different occasions. The estimated population mean was close to the measured one (11.06 ± 1.67 versus 11.32 ± 1.23 g/dL, ). A learning effect could be detected. Relative errors in individual estimates reached, however, up to 50%. Insufficient performance in predicting binary outcomes (ROC AUC: 0.72 to 0.78) and poor interrater reliability (Kappa < 0.6) further characterised this method.